Entirely plasmid-based reverse genetics system for rotaviruses - Kanai, Yuta; Komoto, Satoshi; Kawagishi, Takahiro; Nouda, Ryotaro; Nagasawa, Naoko; Onishi, Misa; Matsuura, Yoshiharu; Taniguchi, Koki; Kobayashi, Takeshi (Proceedings of the National Academy of Sciences - PNAS, 2017)
Rotaviruses (RVs) are highly important pathogens that cause severe diarrhea among infants and young children worldwide. The understanding of the molecular mechanisms underlying RV replication and pathogenesis has been hampered by the lack of an entirely plasmid-based reverse genetics system. In this study, we describe the recovery of recombinant RVs entirely from cloned cDNAs. The strategy requires coexpression of a small transmembrane protein that accelerates cell-to-cell fusion and vaccinia virus capping enzyme. We used this system to obtain insights into the process by which RV nonstructural protein NSP1 subverts host innate immune responses. By insertion into the NSP1 gene segment, we recovered recombinant viruses that encode split-green fluorescent protein–tagged NSP1 and NanoLuc luciferase. This technology will provide opportunities for studying RV biology and foster development of RV vaccines and therapeutics.